2022
DOI: 10.1111/jfpp.16775
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation effect and protective barriers damage caused to Shewanella putrefaciens by stable chlorine dioxide combined with slightly acidic electrolyzed water

Abstract: The present study investigated the inactivation effect and mechanism of stable chlorine dioxide (ClO 2 ) combined with slightly acidic electrolyzed water (SAEW) against Shewanella putrefaciens (S. putrefaciens). The inactivation effect of ClO 2 combined with SAEW against S. putrefaciens was evaluated by the growth curve.The changes in alkaline phosphatase (AKP) activity, transmembrane electrical potential, Na + K + -ATPase activity, confocal laser scanning micrographs (CLSM), β-galactosidase activity, nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Figure 6b also further illustrated the change process of MPs of large yellow croaker during cold storage. However, in our previous study, it has been proved that the ClO 2 and SAEW could significantly inhibit the growth of Shewanella putrefaciens by destroying the bacterial protective barriers (Zhao et al ., 2022). Apart from this, in our current research, it was also confirmed that the inhibition of ClO 2 and SAEW on endogenous protease.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6b also further illustrated the change process of MPs of large yellow croaker during cold storage. However, in our previous study, it has been proved that the ClO 2 and SAEW could significantly inhibit the growth of Shewanella putrefaciens by destroying the bacterial protective barriers (Zhao et al ., 2022). Apart from this, in our current research, it was also confirmed that the inhibition of ClO 2 and SAEW on endogenous protease.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 1a, the growth curve of S. putrefaciens in the CK group was “S‐type” growth, and the growth curve began to increase after 2 h of culture, entered the logarithmic growth phase, then grew rapidly and the OD 600nm significantly ( P < 0.05) increased to 0.94 when it was cultured for 14 h, which is consistent with previous study (Zhao et al ., 2022). The OD 600nm of the CK group was higher than those of other groups.…”
Section: Resultsmentioning
confidence: 99%
“…This result was highly similar to the results of CLSM and the nucleic acid and protein leakage, which indicates that All and AOB can effectively disrupt the cell membrane integrity of S. putrefaciens , thereby increasing the extravasation of intracellular Na + /K + ‐ATPase. Similar results were obtained in a previous study by treating S. putrefaciens with slightly acidic electrolyzed water and stable ClO 2 (Zhao et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further determine the damage degree to cell membrane of S. aureus treated with CS‐g‐CA, bacteria were stained with PI dye and observed by CLSM. PI is a fluorescent probe inserted into DNA, which can only penetrate bacterial cells with damaged cell membranes, and combined with nucleic acid and emitted red fluorescence (Zhao et al, 2022). A few cells of the CK group were dyed red (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%